2021
DOI: 10.1084/jem.20201475
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Gadd45β promotes hyperglycemia and glucose intolerance through DNA demethylation of PGC-1α

Abstract: Although widely used for their potent anti-inflammatory and immunosuppressive properties, the prescription of glucocorticoid analogues (e.g., dexamethasone) has been associated with deleterious glucose metabolism, compromising their long-term therapeutic use. However, the molecular mechanism remains poorly understood. In the present study, through transcriptomic and epigenomic analysis of two mouse models, we identified a growth arrest and DNA damage-inducible β (Gadd45β)–dependent pathway that stimulates hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Mechanistic study revealed that Gadd45β, in conjunction with teneleven translocation 1 (TET1), promotes DNA demethylation of the PGC-1α promoter, thereby stimulating PGC-1α expression and promoting gluconeogenesis and hyperglycemia. 72 In type 2 diabetes mellitus (T2DM) patients, the methylation levels of PGC-1α promoter in skeletal muscle, adipose tissue, and pancreatic islet cells are higher compared to normal individuals. 73,74 Additionally, PPARGC1A methylated DNA/unmethylated DNA ratio in the liver has a significant correlation with plasma fasting insulin levels and homeostasis model assessment of insulin resistance.…”
Section: Upstream Modulators Of Pgc-1smentioning
confidence: 99%
“…Mechanistic study revealed that Gadd45β, in conjunction with teneleven translocation 1 (TET1), promotes DNA demethylation of the PGC-1α promoter, thereby stimulating PGC-1α expression and promoting gluconeogenesis and hyperglycemia. 72 In type 2 diabetes mellitus (T2DM) patients, the methylation levels of PGC-1α promoter in skeletal muscle, adipose tissue, and pancreatic islet cells are higher compared to normal individuals. 73,74 Additionally, PPARGC1A methylated DNA/unmethylated DNA ratio in the liver has a significant correlation with plasma fasting insulin levels and homeostasis model assessment of insulin resistance.…”
Section: Upstream Modulators Of Pgc-1smentioning
confidence: 99%
“…In obese individuals, those with T2D have hypermethylation of the insulin receptor substrate 2 (IRS2) promoter CpG sites in the liver, and the reduced expression of IRS2 is closely related to IR 75 . Among patients with T2D, the elevated expression of DNA damage‐inducible β (Gadd45β), in conjunction with TET1, stimulates the DNA demethylation of the PPARG coactivator 1 alpha (PPARGC1A) promoter, resulting in heightened gluconeogenesis and reduced glucose tolerance among patients 76 . DNAm alterations are evident across all three stages of adipogenesis in obese individuals, and these differentially methylated genes may play a role in the development of T2D primarily by impairing the function of mature adipocytes 77 …”
Section: Dnam In Obesity‐associated Diseasesmentioning
confidence: 99%
“…TET1 was shown to mediate the effects of synergistic treatment with P. gingivalis lipopolysaccharide (LPS) and interferon‐gamma (IFN‐γ) on M1 macrophage polarization 30 . Moreover, TET1 is involved in various diseases, including developmental defects, cancers, inflammation, and metabolic syndromes 31–36 . Based on the above, it is worth investigating whether TET1 is involved in the inflammatory response and pyroptosis elicited by P. gingivalis .…”
Section: Introductionmentioning
confidence: 99%
“…30 Moreover, TET1 is involved in various diseases, including developmental defects, cancers, inflammation, and metabolic syndromes. [31][32][33][34][35][36] Based on the above, it is worth investigating whether TET1 is involved in the inflammatory response and pyroptosis elicited by P. gingivalis.…”
Section: Introductionmentioning
confidence: 99%